Emotion Processing, Reappraisal, and Craving in Alcohol Dependence: A Functional Magnetic Resonance Imaging Study - Jansen, Jochem M.; van den Heuvel, Odile A.; van der Werf, Ysbrand D.; de Wit, Stella J.; Veltman, Dick J.; van den Brink, Wim; Goudriaan, Anna E. (Frontiers in Psychiatry, 2019)
Alcohol dependence has long been related to impaired emotion regulation - including reappraisal - but little is known about the performance and associated neural activity of alcohol dependent patients (ADPs) on an emotion reappraisal task. This study, therefore, compares reappraisal of negative, positive, neutral and alcohol-related images at a behavioral and neural level between ADPs and healthy controls (HCs). Thirty-nine ADPs and 39 age, gender and education matched HCs performed an emotion reappraisal task during functional Magnetic Resonance Imaging (fMRI) and craving was measured before and after the reappraisal task. During the emotion reappraisal task, participants were instructed to either attend or reappraise positive, negative, neutral or alcohol related images, and to indicate their experienced emotion on a VAS scale. Both ADPs and HCs completed the emotion reappraisal task successfully, showing significant differences in self-reported experienced emotion after attending versus reappraising visual stimuli and in brain activity in emotion processing/reappraisal relevant areas. ADPs were not impaired in cognitive reappraisal at a behavioral or neural level relative to HCs, nor did ADPs indicate any difference in self-reported emotion while attending emotional images. However, ADPs were different from HC in emotion processing: ADPs revealed a blunted response in the (posterior) insula, precuneus, operculum and superior temporal gyrus while attending emotional images compared neutral images compared to HCs, and in ADPs higher baseline craving levels were associated with a less blunted response to alcohol related images than in HCs. These results reveal that ADPs do not show impaired reappraisal abilities when instructed, although future studies should assess voluntary reappraisal abilities in alcohol dependent patients.